2017
DOI: 10.1002/anie.201705138
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Side Groups Trigger Second Harmonic Generation Activity in 3D Octupolar Bipyrimidine‐Based Organic Liquid Crystals

Abstract: Abstract.Design of organic noncentrosymmetric materials remains the Holy Grail in the field of second-order nonlinear optics. Unlike inorganic crystals currently used in second-order nonlinear optical applications, organic materials represent an attractive alternative due to their fast electro-optical response and processability, but their alignment into noncentrosymmetric film still remains challenging. Here, symmetry breaking by judicious functionalization of 3D organic octupoles allows the emergence of mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 47 publications
(41 reference statements)
0
14
0
Order By: Relevance
“…30). 76,77 Compounds 75a and 75b with C 12 and C 16 chains exhibit mesomorphic as well as second-order NLO properties in solution (β 0 = 38-42 × 10 −30 esu, measured by hyper-Rayleigh scattering in CH 2 Cl 2 ). Nevertheless, they are SHG silent in their liquid crystalline phases due to the formation of columnar mesophases with hexagonal symmetry.…”
Section: Second Order Nlo Chromophoresmentioning
confidence: 99%
“…30). 76,77 Compounds 75a and 75b with C 12 and C 16 chains exhibit mesomorphic as well as second-order NLO properties in solution (β 0 = 38-42 × 10 −30 esu, measured by hyper-Rayleigh scattering in CH 2 Cl 2 ). Nevertheless, they are SHG silent in their liquid crystalline phases due to the formation of columnar mesophases with hexagonal symmetry.…”
Section: Second Order Nlo Chromophoresmentioning
confidence: 99%
“…Recently, we demonstrated that pseudo‐tetrahedral octupolar compounds presenting donor 3,4‐alkoxystyryl groups attached to 2,2′‐bipyrimidine give rise to liquid crystal and linear and nonlinear optical properties [13] . In another study, we described similar derivatives involving chiral chains at the 3,4 positions, thermodynamically stable liquid crystal phases presenting strong second harmonic generation (SHG) [14] …”
Section: Introductionmentioning
confidence: 99%
“…[13] In another study, we described similar derivatives involving chiral chains at the 3,4 positions, thermodynamically stable liquid crystal phases presenting strong second harmonic generation (SHG). [14] In this present contribution, we describe the synthesis and complete physicochemical characterization (including linear and nonlinear optical, mesomorphic, thermal, structural) of a series of octupolar four-branched compounds incorporating a bipyrimidine (BPM) group as an electron-deficient core (Scheme 1) and four divergent vinyl phenyl arms bearing alkoxy aliphatic chains on position 4. Initially, we described similar derivatives involving chiral chains at the 3,4 positions, thermodynamically stable liquid crystal phases presenting strong second harmonic generation.…”
Section: Introductionmentioning
confidence: 99%
“…This nonlinear response of organic crystals can be applied for various nonlinear optical and electrooptic applications. [1][2][3][4][5][6][7][8][9][10] In the past few decades, many studies on organic nonlinear optical crystals have been carried out to enhance their macroscopic second-order optical nonlinearity toward improving the nonlinear optical performance. [10,11] However, enhancing the macroscopic optical nonlinearity of organic crystals is highly challenging.…”
mentioning
confidence: 99%